Posrnuli suverenitet? Dva slučaja posrnuća suvereniteta nacije države na primjeru Hrvatske - Duško Petrović ([sic], 2022)
Drawing from two historical examples from Croatia, the author examines Wendy Brown’s thesis about waning sovereignty in the contemporary globalized world. In both cases, the author confirms Brown’s thesis. But in order to further examine the thesis about waning sovereignty in the contemporary world, the author identifies what he calls the contemporary signs of waning sovereignty. Then he calls the reader to find these signs in his/her social environment. Keywords: sovereignty, nation-state, post-Westphalian international order, globalization, state of exception, border zonesSuvremeni globalizirani svijet mjesto je djelovanja dviju naizgled isključujućih tendencija: „logike stvaranja moći u globalnoj mreži i logike udruživanja i zastupanja u specifičnim društvima i kulturama” (Castells 21); nadnacionalnog političkog i ekonomskog univerzalizma, kojeg na različite načine zastupaju liberali i neoliberali, kozmopoliti, humanitarci i politički aktivisti, te partikularnog i lokalnog nacionalizma, suverenizma i tradicionalizma (Brown 20).